Effects of night‐time light intensity on the survival rate and stress responses in juvenile Pacific bluefin tuna Thunnus orientalis (Temminck and Schlegel). Issue 7 (21st February 2012) - Honryo, Tomoki; Kurata, Michio; Okada, Tokihiko; Ishibashi, Yasunori
Abstract Land‐based cultured juvenile Pacific bluefin tuna Thunnus orientalis (PBT) have high mortality rates due to collisions or contacts with tank walls after about 30 days of hatching. To determine the effect of night‐time lighting on their survival, juvenile PBT were reared under four different night‐time light intensities (0, 5, 15 and 150 lx) for 9 days, followed by a 3‐day observation period. High‐intensity, night‐time lighting (150 lx) significantly improved the survival rate (75.8%; P < 0.001) compared with the unlit control group (0 lx, 64.3%). The survival rate in the high‐intensity group decreased after the end of the lighting period. Lighting did not influence whole‐body cortisol levels, glucose levels, or diel changes in plasma cortisol levels. In contrast, the survival rates of fish exposed to light intensities between 5 and 15 lx were slightly lower than that of the unlit control group. These results suggest that providing night‐time lighting of 150 lx or higher is an effective method for reducing the mortality of cultured PBT.